2018
DOI: 10.1007/s40430-018-1290-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soft substrate topography on tribological behavior of multifunctional DLC coatings

Abstract: In this study, the influence of soft substrate surface finishing (5 distinct conditions) on tribological properties of hydrogenated amorphous carbon (a-C:H) films is investigated. Low carbon steel substrates were plasma-nitrided and DLCcoated in a single PECVD batch. Topographical evolution was investigated through white light interferometry (WLI) and scanning electron microscopy (SEM). The substrate topography leads to a negligible impact on bonding structure and mechanical properties of a-C:H films, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…According to Al Mahmud et al [47], the higher the ID/IG ratio the greater the number of sp 2 bonds in the ring structure of the film, indicating a reduction in the amount of sp 3 bonds. Soprano et al obtained ID/IG variations from 0.64 to 0.72 with different samples' texturing conditions produced via sanding processes, and indicated that these variations were not significant [29]. The bands' positions (D and G), ID/IG ratio and the percentage of hydrogen in the present work were similar to the values in Soprano´s work.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…According to Al Mahmud et al [47], the higher the ID/IG ratio the greater the number of sp 2 bonds in the ring structure of the film, indicating a reduction in the amount of sp 3 bonds. Soprano et al obtained ID/IG variations from 0.64 to 0.72 with different samples' texturing conditions produced via sanding processes, and indicated that these variations were not significant [29]. The bands' positions (D and G), ID/IG ratio and the percentage of hydrogen in the present work were similar to the values in Soprano´s work.…”
Section: Discussionsupporting
confidence: 83%
“…The combination of multilayers (such as CrN + DLC) increases the loading capacity of the substrate, improving adhesion and leading to a more favorable stress distribution [28]. Plasma nitriding of the substrate is another approach to improve load-bearing capacity before DLC deposition [29]. It allows progressively increase surface hardness, creating mechanical support for the DLC coating [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how the surface finishing (five different conditions) of a soft substrate influences the tribological behavior of hydrogenated amorphous carbon (a-C:H) films, DLC coating was applied on plasma-nitrided low carbon steel substrates. Both processes happened in a single PECVD batch (Soprano et al, 2018). The mechanical properties and bonding structures of the a-C:H films are negligibly affected by the substrate topography.…”
Section: Substrate Surface Finishingmentioning
confidence: 99%
“…The final coating thicknesses reach 5 µm for both coatings. The roughness of the substrate has little effect on the final roughness and thickness of the coating [31]. Coating treatment is done in accordance with the following conditions: vacuum degree 225 Torr, furnace temperature 400 °C, reaction gas N2, plating time 140 min and protection gas N2.…”
Section: Sample Preparationmentioning
confidence: 99%